Numerical Research of Materials Crystal Lattice Parameters Based on Rare-Earth Metals; MATEC Web of Conferences; Vol. 96 : Fundamental Aspects of Rare-Earth Elements Exploration, Mining and Separation and Modern Materials Engineering (REE-2016) - Obkhodskiy A. V. Artem Viktorovich; Popov A. S. Aleksandr Sergeevich; Zolotarev A. A. Alexey Andreevich; Kuznetsov S. G. Sergey Gennadjevich; Sachkov V. I. Victor Ivanovich (2017, 2017)
Title screen